Sequential Modelling of Remote Earth Sensing Process (International Journal of Communication Systems and Network Technologies, 2024)
This paper proposes a method of modelling of remote Earth sensing (RES) process, based on modelling of electromagnetic beam passing through various layers located in between Earth surface and registering sensor, like a number of filters. Such approach allows performing a flexible investigation of RES process, along with providing an ability for scientists to work on models of different layers in parallel in terms of the protocol, defined for inter-filter data flow exchange.
Keywords: Remote Earth Sensing (RES); Sequential Modelling; Electromagnetic Wave Propagation; Micro-Satellites; Linear Image Sensors; Filter-Based Modelling; Satellite Imaging; Beam Refraction; Earth Observation